(3TQM bUjOI GdjOGdi GdUZQi aj eOM GdfHi Udi Gddg Ydjg hSdes - (3eMeO Hf SYjO GdjOGd Hf eNJGQ, GdjOGdj GdjOjeGfs
(3ChdgG (B:s
(3hHYO aGf eOMg Udi Gddg Ydjg hSde ef GaVd GdCYeGd hGLd eG jJhSd Hg abO cfJ eOMJg HbUjOJjf ejejJjf JHQckG HMQajf ef GSeg s
(3BNQgG (B:s
(3Udi Ydjc Gddg eGfM GdQLG VhA GdUHGM GdeSJfjQ GdXGgQ s
(3GdbUjOI hGdTQM dgs
(3HBNQ UaMGJgG JYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B176 s
Keywords: (3GdCOHs